Methodology for removing microplastics and other anthropogenic microparticles from sludge dewatering system. (15th July 2022) - Bretas Alvim, C.; Valiente, S. Navajas; Bes-Piá, M.A.; Mendoza-Roca, J.A.
Abstract: Anthropogenic microparticles (e.g., microplastics) are present in sewage plants, especially in sludge streams. However, the lack of standardized protocols to scrutinize the presence of anthropogenic microparticles in sludge makes the comparison between studies unfeasible. To tackle the knowledge gap regarding the efficiency of methodologies on the extraction of anthropogenic microparticles from the complex organic matrix, dewatered sludge, and digested sludge was treated with peroxidation and density separation, and the recovery of microparticles from these samples was investigated. The results showed that with the use of a higher density solution (NaI, 1.5 g/cm 3 ) a much better recovery of anthropogenic microparticles from sludge samples (approximately 1000 microparticles/g-dw and 2000 microparticles/g-dw, from dewatered and digested sludge, respectively) was achieved in comparison with the use of a lower density solution (NaCl, 1.2 g/cm 3 ) (200 microparticles/g-dw and 600 microparticles/g-dw from dewatered and digested sludge, respectively). Moreover, although the use of peroxidation is an essential step to break down the sludge structure and to release microparticles to the liquid phase, the use of peroxidation after or before density separation did not affect the overall recovery of microparticles. Polyethylene, polypropylene, and copolymer ethylene-ethyl-acrylate were the main microplastic fragments identified in digested sludge and dewatered sludge. However, no relation was observed between the method applied and the polymer recovered. Regarding the presence of anthropogenic microparticle in centrifuge effluent, 450 ± 212 microparticles/L were counted, and although little is known about this stream, in can be a relevant source of anthropogenic microparticles. Highlights: Methodologies for extracting microparticles from sludge samples were investigated. Higher density solution recovers more microparticles from sludge samples. Peroxidation is an essential step to release microparticles to the liquid phase. Centrate can be an important input of microparticles back to WWTPs.